İSTANBUL ÜNİVERSİTESİ TÜP BEBEK ARAŞTIRMA VE UYGULAMA MERKEZİ 1996 İN VİTRO FERTİLİZASYON (IVF) SONUÇLARI - ÖÇAL, Pelin; ÇEPNİ, İsmail; İDİL, Mehmet; İREZ, Tülay; ŞENOL, Hülya; YALDIR, Fatma; ELİBOL, Feyhan; AKSU, Feridun (Cerrahpaşa Medical Journal, 2014)
Background. The aim of this study is to present the results of in vitro fertilization and embryo transfers (IVFET) carried out at Istanbul University IVFET Research and Practice Center in 1996 and to determine the factors affecting success by analyzing the characteristics of our infertile population. Design. 326 IVF cycles were applied to 285 infertile couples in 1996. Relation of women age, infertility duration, cause of infertility, ovulation protocol, number of human menopausal gonadotropin ampules number of available oocytes fertilization rate (FR) and pregnancy rate (PR) was evaluated. The effect of fresh sperm densitiy, sperm parameteres total motile sperm after washing in relation to fertilization and pregnancy outcome was determined. Results. In 326 IVF cycles, transfer rate was 45% and pregnancy rate with respect to transfer was 17%. There was a significant relation between advanced women age and pregnancy (p<0.002) and between available oocyte and pregnancy (p<0.0012). When sperm density was less than 20 million/ml, 17.7 % fertilization and 2.2% pregnancy, when sperm density was more than 20 million/ml 50% fertilization and 9% pregnancy occurred (p<0.01). When motility was less than 50% fertilization rate was 45% and pregnancy rate was 7%, when motility was more than 50% fertilization rate was 58% and pregnancy rate was 25% (p<0.005). When available total motile sperm amount after preparation was less than 5 million/ml 24% fertilization and 6% pregnancy; 5 to 10 million/ml 27% fertilization and 4% pregnancy, more than 10 million/ml 64% fertilization and 10% pregnancy occurred. In 93% of our cases there was male factor. Conclusion. Success rates in IVF varies according to women age, oocyte number and degree of male factor.